ANALYSIS OF THE SYMBOLIC ATTRIBUTES AND TIFO OF LA GRANDE INDONESIA IN THE INDONESIA NATIONAL TEAM VS BAHRAIN MATCH AT GELORA BUNG KARNO STADIUM IN 2025 - Rafrizar Abdul Ghani; Dwi Budi, Budiharto (Universitas Negeri Semarang, 2025)
This study examines the role of qualitative methods and semiotic analysis in investigating the symbolic attributes and tifos created by La Grande Indonesia (LGI) during the Indonesia vs. Bahrain football match on March 25, 2025, at Stadion Gelora Bung Karno, with a focus on conveying messages of national identity, supporter solidarity, and patriotism. Employing Roland Barthes’ semiotic framework, the research analyzes primary data from direct observations, photographic documentation, and Instagram content from official LGI and illustrator accounts, supplemented by secondary data from academic literature and media archives. Key visual elements, including the Garuda symbol, the colors red and white, and banners such as “Garuda Fly Alone, Bulbuls Flock Together” and “Jaya Raya Indonesia,” were decoded across denotative, connotative, and mythic levels. The findings reveal that the Garuda symbolizes national strength and independence, while collective displays of flags and tifos foster a sense of solidarity among supporters. The “Jaya Raya Indonesia” banner, tied to a 1-0 victory, reinforces a mythic narrative of national pride and love for the homeland. Triangulation of data sources ensured validity, confirming that these symbols and attributes serve as powerful communicative tools that extend beyond aesthetics to embed cultural values within the sporting context. The study concludes that semiotic analysis effectively uncovers the deep meanings embedded in tifos and banners, highlighting their role in mobilizing nationalistic sentiments and collective identity among Indonesian supporters. This approach highlights the importance of qualitative methods in examining the sociocultural aspects of sports, providing insights into how visual symbols shape and reflect national consciousness in competitive contexts.